Long-term antidepressant treatment in general practice: changes in body mass index. (December 2016) - Chiwanda, Laura; Cordiner, Matthew; Thompson, Anne T.; Shajahan, Polash
Abstract : Aims and method: To discern changes in body mass index (BMI) in patients on long-term antidepressant treatment in a general practice population and establish BMI changes in patients with and without a diagnosis of diabetes. We used a retrospective observational method and identified patients on four antidepressants of interest. We excluded those who did not have start and current BMI readings within the past 3 years and noted whether or not patients had a diagnosis of diabetes. Results: Long-term treatment with citalopram, fluoxetine, mirtazapine and sertraline was associated with increased BMI in two-thirds of patients. There was reduction in BMI in patients with diabetes and an increase in BMI for patients who did not have diabetes. Clinical implications: Awareness of environmental factors and their impact on individuals is important. Medication is not the only cause of abnormal metabolic effects. Overall monitoring of physical health is important in all groups of patients.